Influential factors to occupy green residential building among green building occupants - Azis, Shazmin Shareena Ab.; Zulkifli, Nur Amira Aina; Rahman, Nur Hannani Ab. (Environmental and Toxicology Management, 2021)
Green building has been proven having higher occupancy rate than conventional building. The occupancy rate of ENERGY STAR and LEED-certified green office building are 8% to 18% higher than conventional office building. Previous research has proved that occupants prefer to occupy green office building due to various green benefits. However, most of these researches were conducted on green office building. Therefore, this study is motivated to identify the influential factors for occupants to occupy green residential building. The aim of this study is to evaluate factors that influence occupants to occupy green certified residential building. 75 questionnaires were distributed among occupants of green certified residential building namely Molek Pine 4 and Ponderosa Lakeside Apartment in Johor Bahru. The results were analysed using frequency analysis. Location and good environment quality are the most significant factors that influence occupants to occupy the green certified residential building in Johor Bahru. This research is noteworthy for property industry players especially property developer in guiding the direction of green residential building development in accordance with occupants’ and market preferences.